Dr. Philippe Hamel and the Public Power Movement in Quebec City, 1929-1934: The Failure of a Crusade - Dirks, Patricia (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
The fight over municipalization of electrical services in Quebec City waged between 1929 and 1934 grew out of the determination of a prominent dentist, Dr. Philippe Hamel, to rescue his fellow citizens from the grip of the electricity trust. Initially Hamel's attack on the Quebec Power Company, in a monopoly position in Quebec City after 1923, received support from local businessmen's associations with the notable exception of the Board of Trade. Quebec Power's co-operation in the board's schemes to attract new big business ventures to Quebec City and Hamel's favourable disposition toward government-run electrical utilities combined to produce a bitter confrontation when the city administration appeared to be responding positively to his campaign. Ultimately divisions within the business community, personality clashes, and political rivalries contributed to the success of Quebec Power's carefully orchestrated defence of its interests carried out at the provincial as well as the municipal level of government.Hamel's involvement in the French-Canadian nationalist movement and his association with L'École Sociale Populaire during the 1930s added a unique dimension to the attack he led against the electricity trust in Quebec City. The crusading nature of his drive to secure government-run competition in the electricity field proved to be an effective weapon in the hands of Quebec Power and its allies and thus contributed to the failure of the public power movement spearheaded by Hamel in Quebec City in these years.